Microservices caching for container-based IoT system in the edge and cloud - Qasha, Rawaa; Sulyaman, Haleema (Institute of Advanced Engineering and Science, 2025)
Microservices enable agile development by dividing internet of things (IoT) programs into autonomous components, ensuring fault tolerance and parallel operation for enhanced productivity. Their adaptability across diverse service types and applications improves IoT system performance. On the other hand, the container is the preferred solution for microservices-based enterprises. To improve the effectiveness of the deployment system presented in our paper 1, we developed a new caching technique to significantly optimize the performance of the deployment system and automate the sharing and re-using of ready-to-run microservices that have been packaged as Docker images. The new caching techniques are seamlessly integrated with our deployment system to optimize the microservices caching of the IoT application by utilizing Docker-based container virtualization and Redis for consistent data sharing. In addition, DevOps and versioning tools such as GOCD and GitHub are integrated into our system to enhance the automatic deployment of the microservices resulting in self-contained, portable, and repeatable IoT microservices. The effectiveness of the proposed techniques is evaluated via various experiments implemented in various working environments where the results show reduced deployment time and the effort required to re-execute the microservices, in addition to the reduction of burden and error that occur when adopting a manual deployment.